Penerapan Sistem Kendali XY-Stage dan Modulasi Laser Pada Tomografi Fotoakustik Menggunakan Arduino - Gong Matua; Triyogatama Wahyu Widodo; Mitrayana Mitrayana (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2017)
Photoacoustic tomography is a system of utilization of the photoacoustic effect is used to obtain image-processing with high resolution and contrast. The purpose of studies is to design a mechanics xy-stage and implement control systems in laser modulation. The system design consists of designing hardware and software. Hardware design includes the design of optical devices and the design of electronic devices using the Arduino microcontroller. Software design using Arduino IDE, Audacity and Matlab. Recording test results showed that the photoacoustic signal peaks on the recording with the samples was higher than the recording unsampled. Based on the test mileage xy-stage mechanical movement using a type of bipolar stepper motor Nema 17, earned mileage (4.046 ± 0.005) mm for the motor movement for one revolution and it takes 25 steps to obtain the distance as far (0.50 ± 0.05) mm used on scanning process. Image-processing has been able to show the results of the image corresponding to the scanning area, the process is carried out on the object-imaging soft tissues such as the pancreas with cell tumor tissue.